PENGEMBANGAN DAKWAH DALAM MENJAWAB TUNTUTAN MASYARAKAT KONTEMPORER - Wisri; Abdul Mugni Shaleh (Al'Adalah, 2015)
Dakwah Islamiyah (Islamic Propagation) especially in terms of it’s signifycant in the era of contemporary is considered to be very important. The third millennium era called too an era of global be the concept as representation of phenomena of the world that according to John Naisbit characterized by the appearance of interdependence in almost all dimensions of life, and in the relations both nation state, as well as the transnational relations. This condition is not avoid also affect thought and performance Dakwah Islamiyah (Islamic Propagation). There was no doubt that the era of contemporary on some progress of science and technology as well as industry which is quite rapidly, driven more advanced and the modernization of the religious life, especially it’s bright. Should to realized that Dakwah activities would not be last in this time if Dakwah was not respond to problems that acquirable by in the era of contemporary today. Therefore, this is the urgency the implementation of the Dakwah so as to have applicable protect power to the challenges and threat due to the contemporary era.